The Implementation of Teacher Performance Assessment Using PMM/Ruang GTK at SMP Negeri 2 Pamotan - Supriati, Ana; Safikin; Astuti, Yanti Yuni; Nurkolis (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the implementation of teacher performance assessment using the Merdeka Mengajar Platform (PMM)/Ruang GTK at SMP Negeri 2 Pamotan. Given the pivotal role of teachers in improving the quality of education, performance assessment is essential to ensure professional accountability and instructional effectiveness. The study adopts a qualitative case study approach to examine how the platform has been utilized to support teachers’ reflective practices, competency development, and documentation of performance evidence. Data were collected through in-depth interviews, observations, and document analysis involving key informants, including school principals, vice principals, supervisors, and senior teachers. Findings reveal that since its implementation in 2024, the PMM/Ruang GTK system has gradually been integrated into the school’s performance evaluation processes. The platform is appreciated for its transparency, accessibility, and alignment with national digital governance policies. However, challenges persist, such as limited digital literacy among teachers, inadequate internet infrastructure, and time constraints in technical mentoring. The study emphasizes the active role of school leadership and peer collaboration in facilitating the transition from conventional to digital evaluation practices. Overall, the PMM/Ruang GTK platform presents a promising tool for promoting professional reflection and performance management in schools. Its successful implementation, however, requires consistent support, capacity-building programs, and evaluation mechanisms to ensure its effectiveness in enhancing educational quality. The study contributes to the academic discourse on the integration of digital platforms in teacher performance evaluation, recommending ongoing mentoring and infrastructure enhancement to maximize the platform's impact on teacher performance and learning outcomes.